2021
DOI: 10.1186/s12879-021-06841-x
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus gastroenteritis hospitalizations in provinces with different vaccination coverage rates in Spain, 2013–2018

Abstract: Background Rotavirus (RV) vaccines are available in Spain since 2006 but are not included in the National Immunization Program. RV vaccination has reached an intermediate vaccination coverage rate (VCR) but with substantial differences between provinces. The aim of this study was to assess the ratio of RV gastroenteritis (RVGE) admissions to all-cause hospitalizations in children under 5 years of age in areas with different VCR. Methods Observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Modelling these elements has helped to clarify the indirect effects of the vaccine that increase or reduce the herd effect, influencing the net vaccine effect and explaining the appearance of new disease peaks over time with a shift to older children as the primary source of infection [ 22 ]. The data from Spain confirm the findings in Belgium with a sub-optimal launch of rotavirus vaccination [ 32 , 47 ]. The data from Finland and the UK may prove that initiating the vaccine programme earlier in the year and with an immediately high coverage achieves greater reductions in hospitalisation, compared with what was observed in Belgium [ 38 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Modelling these elements has helped to clarify the indirect effects of the vaccine that increase or reduce the herd effect, influencing the net vaccine effect and explaining the appearance of new disease peaks over time with a shift to older children as the primary source of infection [ 22 ]. The data from Spain confirm the findings in Belgium with a sub-optimal launch of rotavirus vaccination [ 32 , 47 ]. The data from Finland and the UK may prove that initiating the vaccine programme earlier in the year and with an immediately high coverage achieves greater reductions in hospitalisation, compared with what was observed in Belgium [ 38 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 81%
“…Countries across Europe have launched rotavirus vaccination programmes that differ from the Belgian launch in their initial vaccine coverage rates and date of initiating the vaccination programme. Figure 7 A shows hospitalisation rates in the vaccine uptake period in three other countries in Europe that introduced rotavirus vaccination and for which data were available in the public domain [ 30 , 31 , 32 ]. Figure 7 B shows the results when these data are applied in the model for the full 13-year period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed a significant health resource utilization and costs related to the management of severe cases of RVGE requiring hospital treatment in a country with intermediate vaccination coverage rate. Results from a previous analysis in the hospitals participating in this study, published elsewhere, 10 showed that the RVGE-related hospitalization ratios were highly dependent on the vaccination coverage rates, suggesting that the increase in the vaccination coverage rate would significantly impact the related healthcare resource utilizations and costs.…”
Section: Discussionmentioning
confidence: 73%
“…They are used under pediatricians’ recommendations and fully paid by parents, reaching an intermediate vaccination coverage rate with significant differences among regions. It has been shown that, in this context of suboptimal vaccination, the burden of hospitalization due to RVGE in Spain is still relevant 10 and, therefore, may lead to a substantial economic impact to the healthcare system.…”
Section: Introductionmentioning
confidence: 99%